Analisis Pelaksanaan Program Upaya Khusus Padi, Jagung, Kedelai (Upsus Pajale) dalam Mewujudkan Swasembada Pangan di Kabupaten Sidenreng Rappang - Muh. Rezky; Andi Samsu Alam (Departemen Ilmu Pemerintahan Fisip Unhas, 2019)
The aim of this research is to know and analyze the implementation of special effort program Rice, Corn, Soybean (UPSUS PAJALE) in realizing self-sufficiency of food in Sidenreng Rappang Regency (case study: Pitu Riawa and Pitu Riase sub-district) and to know and analyze what factors which influences the implementation of special effort program of Rice, Corn, Soybean (UPSUS PAJALE) in realizing food self-sufficiency in Sidenreng Rappang Regency (Case study: Pitu Riawa Sub-district and Pitu Riase Sub-district). The type of research is qualitative. Technique of collecting data by observation, interview and documentation study. Data analysis technique using qualitative descriptive approach. The result of the research shows that the implementation of special effort program of Rice,Corn,Soybean (UPSUS PAJALE), in realizing food self-sufficiency in Sidenreng Rappang Regency there are seven activities carried out namely: Irrigation network development activities have been implemented according to technical guidance of implementation based on UPSUS guidance so that categorized the implementation of the program runs well. Land optimization activities are additional planting in accordance with the needs of farmers and able to increase productivity and production for rice commodities, so can be categorized the implementation of the program runs well. Optimization activities of planting area extension of soybean through increased cultivation index (PAT-PIP Soybean) have been carried out in accordance with the technical guidelines of implementation based on UPSUS guidelines. However, PAT-PIP Soybean has not been maximally implemented in Sidenreng Rappang Regency. The Corn Plantation Extension (PAT-Corn) activity has been carried out in accordance with the technical guidelines for implementation based on UPSUS PAJALE guidance. Integrated Crop Management Application (GPPTT) of rice, corn and soybean activities have been implemented in accordance with the technical guidelines of implementation based on UPSUS guidance, GPPTT activities can be categorized as good program implementation. Activities Provision of agricultural facilities and infrastructure (seeds, fertilizers, pesticides, agricultural tools and machinery) has been carried out in accordance with the technical guidance of the implementation so that it can be categorized as good. Escort and mentoring activities have been carried out in accordance with the technical guidelines of implementation based on UPSUS guidelines for increasing rice, corn and soybean production. Can be categorized as good but needs to be optimized and What factors affect the implementation of special effort program of Rice, Corn, Soy (UPSUS PAJALE) include: Farmer Knowledge Factor and Coaching and Supervision Factor.